Which Roots Penetrate the Deepest in Rice and Maize Root Systems? - Hideki Araki; Masakata Hirayama; Hideo Hirasawa; Morio Iijima (Plant Production Science, 2000)
Deep penetration of an axile root is one of the important factors that allow crops to form deep root systems. In this study, the nodes from which the deepest penetrated roots had emerged were examined at the heading stage in upland rice and maize grown in large root boxes and in the field. Both experiments were designed to measure the direction, length, and rooting nodes of each root. In maize, the growth angles of axile roots increased with vertical elongation as rooting nodes acropetally advanced. The roots that emerged from the lower nodes, namely from coleoptilar to the second node, exhibited conspicuously horizontal elongation in the field, reaching 2.3 m in width at the maximum. The roots that emerged from higher than the fifth node were too short to penetrate deeply. Thus, these roots became the deepest root in less or no probability under field conditions. On the other hand, the fourth nodal root, which had an intermediate growth angle and length, had the highest probability. In upland rice, the deepest roots emerged from the nodes lower than the forth node on the main stem in the root boxes. In the field, however, the deepest roots emerged at later stages, that is, the roots from the middle nodes on the main stem and from the low nodes on the primary and secondary tillers were the deepest roots. Five out of nine of the deepest roots were from the prophyll nodes in three field-grown upland rice. The deepest roots from the same plant were estimated to have emerged and grown at approximately the same stage.